Peningkatan Toleransi Dua Varietas Padi Terhadap Cekaman Terendam Melalui Perlakuan Pemupukan Pada Lahan Rawa Lebak - Gribaldi Gribaldi; Nurlaili Nurlaili (Research Center for Suboptimal Lands (PUR-PLSO), Universitas Sriwijaya, 2016)
Gribaldi et al, 2016. Tolerance Improvement of Two Rice Varieties to Submerged Stress Through Fertilization Treatment in Swamp. JLSO 5(1):1-9.Rice plants tolerance to the submerged conditions need to be improved in order to minimize the crop damage during the immersion. To increase the tolerance of rice plants effort is required to produce a good plant growth and early high vigor before the immersion, one through fertilization treatment. This study aims to obtain proper fertilization technology that can increase stress tolerance of rice plants submerged in swampy embankment conditions. The experimental design used in this study is the split plot design with three replications. The main plot is the fertilization treatment (P) consists of; P0 = full doses of N fertilization without submerged, P1 = full doses of N fertilization with submerged, P2 = ½ doses of N fertilizer with submerged. The subplots are varieties of rice (V) consist of; V1 = Variety of Inpara 5, V2 = Variety of IR 64. The results of the study showed that fertilization treatment affect on rice plants tolerance to stress submerged, ½ doses of N fertilizing may increase the tolerance of crops to submersion stress, Variety of Inpara 5 tends to be more tolerant to submersion stress than the varieties of IR 64 at various fertilization treatment.